Ethics and Digital Transition: Some Thoughts on the Past for the Future - du Marais, Bertrand (International Transitions, 2024)
After an introduction outlining the definitions of «transition» and «ethics» adopted in this paper within the specific context of the information society and the digital economy, the first part of this contribution will seek to assess the evolution of the information society, during which it has gradually become clear that the promises of the Internet have only been partially fulfilled. Among the various causes of this deviation, the second part will focus specifically on the initial decision to exempt information society operators, particularly those handling content, from any editorial responsibility. This legal framework has, since the dawn of the Internet, and even more so today, given rise to risks and pathologies that raise significant ethical concerns. In conclusion, the various ethical issues identified in this article are situated within the broader problem of what the author calls «The Great Avoidance»: a paradigm in which modern societies increasingly find themselves governed by a principle of social life and a legal practice that aim to avoid, by any means, especially digital ones, direct face-to-face interactions between individuals.